Goy Israel's multiple others and the birth of the gentile - Ofir, ʿAdi 1951-; Rozen-Tsevi, Yishai 1971- (Oxford Oxford University Press, 2018)
This volumes traces the development of the term and category of the goy from the Bible to rabbinic literature. Adi Ophir and Ishay Rosen-Zvi show that the category of the goy was born much later than scholars assume; in fact not before the first century CE. They explain that the abstract concept of the gentile first appeared in Paul's Letters. However, it was only in rabbinic literature that this category became the centre of a stable and long standing structure that involved God, the Halakha, history, and salvation. The authors narrate this development through chronological analyses of the various biblical and post biblical texts (including the Dead Sea scrolls, the New Testament and early patristics, the Mishnah, and rabbinic Midrash) and synchronic analyses of several discursive structures
Includes bibliographical references and index
This edition previously issued in print: 2018
Zielgruppe - Audience: Specialized
Keywords: Gentiles in the Bible; Gentiles in rabbinical literature; Gentiles in the Bible; Gentiles in rabbinical literature